Complete mitochondrial genome of Morphostenophanes sinicus (Zhou, 2020) (Insecta: Coleoptera: Tenebrionidae). Issue 10 (3rd October 2021) - Bai, Yu; Gao, Xuyuan; Yu, Yonghao; Long, Xiuzhen; Zeng, Xianru; Wei, Dewei; Ye, Lin
Abstract: The genus Morphostenophanes is a small arboreal group of darkling beetles that are endemic to the Oriental region. The complete mitochondrial genome of the M. sinicus population from the Manwan Town was first characterized. The mitogenome consisted of a circular DNA molecule of 15, 662 bp with a 66.352% AT content. It comprises 13 protein-coding genes (PCGs), 22 tRNA genes, and two rRNA genes. The PCGs have a typical ATN (Met) start codon, except for nad1 (TTG as a start codon), and are terminated by typical TAN stop codons.